Depression in Thai patients with rheumatoid arthritis - Khongsaengdao B. (2014)
A wide spectrum of behavioral and psychological disturbances, in particular depression, has been described as a prevalent problem in patients with rheumatoid arthritis (RA). The investigators proposed to evaluate the correlations of depressive symptoms and the disease activity of RA in Thai patients. A variety of aspects of disease activity included in the assessment were the number of swollen joints, the number of tender joints, overall tenderness of the joints (assessed by using the Ritchie Articular Index), overall pain (assessed by using the visual analog scale for pain), joint functional class, and disease duration. The 24-item Hamilton Rating Scale for Depression (HRSD) was the measure used to determine the severity of depressive symptoms. The correlations of HRSD scores and the data relevant to the disease activity were evaluated by using Pearson correlation test. A total of 75 female and 4 male patients participated in this study. Their mean age and mean duration of disease were 49.81 and 7.48 years, respectively. The mean score of HRSD was significantly correlated with those of the number of swollen joints, the number of tender joints, the Ritchie Articular Index, the visual analog scale for pain, and the joint functional class. In conclusion, depression is highly correlated with some respects of the disease activity of RA, especially the number of swollen joints and joint functional class. The results of the present study are not much different from those of previous studies conducted in western countries. Careful evaluation of the disease activity of RA will be helpful in detecting the depression comorbidity in Thai patients suffering from this disease.